Examining purposeful researchable questions in mathematics education - Ramsay-Jordan, Natasha; Crenshaw, Andrea; Chestnutt, Cliff (Journal of Honai Math, 2022)
Often general, and frequently involving scholarly concepts, research questions are the cornerstone of studies. Thus, from their precise wording to their context, research questions play a vital role in uncovering information, determining answers given by participants, and drawing conclusions. However, poorly structured research questions and misalignments to purpose within theoretical and empirical studies can lead to miscommunication and unanswered queries. To this point, this paper discusses the importance of asking purposeful researchable questions in mathematics education and examines what purposeful questioning in mathematics education using quantitative and qualitative research designs entails. An extensive review of literature, is presented with the purpose of identifying strategies for asking purposeful questions, exploring various criteria for judging researchable questions in mathematics education, and discussing the importance of aligning research questions to methodology and frameworks. The key findings reveal that ambiguities of language and the powerful force of context in interpreting the meaning of questions and answers could influence the impact of studies. Implications exist for mathematics and science education scholars who, face various challenges in asking questions that will produce what they want to know. The paper concludes with a brief discussion as to the significance and possibilities of purposeful researchable questions in mathematics education.